Oral health education: community and individual levels of intervention - Veiga, N. (2015)
Introduction: Oral health education is an important issue that should be discussed with children and adolescents, promoting the acquisition of correct oral health behaviors. The objective of this study was to characterize the oral health behaviors among a sample of Portuguese adolescents and introduce different strategies that enable the accomplishment of collective programs appropriate for the promotion of oral health at individual and community levels. Materials and Methods: A cross-sectional study was designed with a sample of 447 adolescents aged 12 to 19 years old, attending a public school in Sátão, Portugal. An interview was made questioning about socio-demographic factors and oral health behaviors to each adolescent. Considering the obtained results, a revision of the literature was made in order to define oral health promotion strategies to be applied among children and adolescents to improve oral health behaviors in a specific Portuguese community. Results: The prevalence of toothbrushing (twice-a-day or more) was 90.6%. Five point eight percent of adolescents reported daily flossing. Sixty-seven percent had at least one dental appointment in the previous twelve months. Considering the results obtained, various oral health promotion strategies should be developed based on the following topics: oral health education for children and adolescents in schools and public institutions; oral health promotion for teachers and parents; technology application in oral health education; education and motivation for oral health behaviors given by health professionals. Conclusions: Community programs should be considered and developed in order to improve knowledge and behaviors related to adolescents’ oral health, giving special attention to the intervention of various health professionals, teachers and parents in the oral health education that should be transmitted to children and adolescents.